Convergence analysis of the iterative methods for quasi complementarity problems - Muhammad Aslam Noor (International Journal of Mathematics and Mathematical Sciences, 1988)
In this paper, we consider the iterative methods for the quasi complementarity problems of the formu−m(u)≥0,   T(u)≥0,   (u−m(u),T(u))=0,where m is a point-to-point mapping and T is a continuous mapping from Rn into itself. The algorithms considered in this paper are general and unified ones, which include many existing algorithms as special cases for solving the complementarity problems.